Practical management of patients with myelofibrosis receiving ruxolitinib. Issue 5 (October 2013) - Harrison, Claire; Mesa, Ruben; Ross, David; Mead, Adam; Keohane, Clodagh; Gotlib, Jason; Verstovsek, Srdan
Myelofibrosis (MF) is characterized by bone marrow fibrosis, progressive anemia and extramedullary hematopoiesis, primarily manifested as splenomegaly. Patients also experience debilitating constitutional symptoms, including sequelae of splenomegaly, night sweats and fatigue. Ruxolitinib (INC424, INCB18424, Jakafi, Jakavi), a JAK1 and JAK2 inhibitor, was approved in November 2011 by the US FDA for the treatment of intermediate- or high-risk MF, and more recently in Europe and Canada for the treatment of MF-related splenomegaly or symptoms. These approvals were based on data from two randomized Phase III studies: COMFORT-I randomized against placebo, and COMFORT-II randomized against best available therapy. In these studies, ruxolitinib rapidly improved multiple disease manifestations of MF, reducing splenomegaly and improving quality of life of patients and potentially prolonging survival. However, as with other chemotherapies, ruxolitinib therapy is associated with some adverse events, such as anemia and thrombocytopenia. The aims of this article are to provide a brief overview of ruxolitinib therapy, to discuss some common adverse events associated with ruxolitinib therapy and to provide clinical management recommendations to maximize patients' benefit from ruxolitinib.